2012
DOI: 10.1039/c2cp23421a
|View full text |Cite
|
Sign up to set email alerts
|

A method for finding the ridge between saddle points applied to rare event rate estimates

Abstract: A method is presented for finding the ridge between first order saddle points on a multidimensional surface. For atomic scale systems, such saddle points on the energy surface correspond to atomic rearrangement mechanisms. Information about the ridge can be used to test the validity of the harmonic approximation to transition state theory, in particular to verify that second order saddle points-maxima along the ridge-are high enough compared to the first order saddle points. New minima along the ridge can also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…( 7) numerically. In a different setting, the corrections to TST rates that are due to rank-2 saddles were recently estimated by Maronsson et al [40], who calculated the energy ridge that connects the rank-1 saddle to the rank-2 saddles. In contrast to ours, their method takes account of the precise shape of the potential along the ridge.…”
Section: B Calculation Of the Reaction Ratementioning
confidence: 99%
“…( 7) numerically. In a different setting, the corrections to TST rates that are due to rank-2 saddles were recently estimated by Maronsson et al [40], who calculated the energy ridge that connects the rank-1 saddle to the rank-2 saddles. In contrast to ours, their method takes account of the precise shape of the potential along the ridge.…”
Section: B Calculation Of the Reaction Ratementioning
confidence: 99%
“…For cases where a suitable distinguished coordinate can be found that leads to a SPP that smoothly connects the first-and second-order saddle points, we expect that the SPP will serve as a useful starting point for a fully, variationally optimized, global dividing surface. We note that Maronsson et al 33 have recently reported a rigorous algorithm for following ridges between two first-order saddle points. These ridges can be considered as an analogue of the IRC, just as the distinguished coordinate SPP is the analogue of the MEP.…”
Section: Introductionmentioning
confidence: 97%
“…A recent paper of Maronsson et al (118) provides an algorithm for finding an index-two saddle point on a (1D) ridge connecting two index-one saddle points. Note that this algorithm does not prove that the existence of two index-one saddles implies that there is a ridge connecting them that contains an index-two saddle.…”
Section: The Roaming Saddle and Its Role In Roamingmentioning
confidence: 99%